Adjusted bacterial cooperation in anammox community to adapt to high ammonium in wastewater treatment plant - Yiming Feng; Lingrui Kong; Ru Zheng; Xiaogang Wu; Jianhang Zhou; Xiaochen Xu; Sitong Liu (Water Research X)
Bacterial cooperation is very important for anammox bacteria which perform low-carbon and energy-efficient nitrogen removal, yet its variation to adapt to high NH4+-N concentration in actual wastewater treatment plants (WWTPs) remains unclear. Here, we found wide and varied cross-feedings of anammox bacteria and symbiotic bacteria in the two series connected full-scale reactors with different NH4+-N concentrations (297.95 ± 54.84 and 76.03 ± 34.01 mg/L) treating sludge digester liquor. The uptake of vitamin B6 as highly effective antioxidants secreted by the symbiotic bacteria was beneficial for anammox bacteria to resist the high NH4+-N concentration and varied dissolved oxygen (DO). When NH4+-N concentration in influent (1785.46 ± 228.5 mg/L) increased, anammox bacteria tended to reduce the amino acids supply to symbiotic bacteria to save metabolic costs. A total of 26.1% bacterial generalists switched to specialists to increase the stability and functional heterogeneity of the microbial community at high NH4+-N conditions. V/A-type ATPase for anammox bacteria to adapt to the change of NH4+-N was highly important to strive against cellular alkalization caused by free ammonia. This study expands the understanding of the adjusted bacterial cooperation within anammox consortia at high NH4+-N conditions, providing new insights into bacterial adaptation to adverse environments from a sociomicrobiology perspective.